Legal Protection Analysis of Consumers Against Traditional Medicines Containing Pharmaceutical Chemical Substances (BKO) in Digital Markets - Tiara; Ali, Nuraliah; Nugraha, Satriya (Dinasti Research, 2025)
Pharmaceutical Chemical Substances (BKO) are chemicals added to traditional medicines to enhance their efficacy and accelerate healing. A 2015 BPOM (Indonesian Food and Drug Authority) report found 54 traditional medicine products containing BKO circulating in digital markets, posing potential risks such as liver and kidney damage. This study examines the legal protection of consumers against traditional medicines with BKO in digital markets and evaluates BPOM's role in prevention. The research uses a normative juridical method with a statute approach, analyzing secondary data qualitatively. Findings show that consumer protection for traditional medicines with BKO in digital markets is regulated under Law No. 8 of 1999 concerning Consumer Protection (UUPK), particularly Article 19, which prohibits businesses from making false or misleading claims. The Electronic Information and Transactions Law (UU ITE) also applies, particularly Article 9, requiring full disclosure to consumers regarding the substances, approval, form, efficacy, and side effects of the medicine. Sanctions for businesses selling traditional medicines with BKO in online markets can be imposed to protect consumer rights. Consumers are entitled to legal protection for purchasing traditional medicines not registered with BPOM. Articles 60 to 63 of the UUPK specify administrative and criminal sanctions, with Article 60 outlining administrative sanctions and Articles 61 and 62 detailing criminal penalties. BPOM issued Regulation No. 8 of 2020 to supervise online food and drug distribution, aiming to prevent the circulation of traditional medicines with BKO. BPOM Regulation No. 14 of 2024 revokes the previous regulation, expands commodity coverage, and clarifies procedures for monitoring and withdrawing illegal products based on online verification